Did the crisis induce credit rationing for French SMEs? - Kremp, Elizabeth; Sevestre, Patrick (Journal of Banking & Finance, 2013)
This paper focuses on the access of independent French SMEs to bank lending and analyzes whether the observed evolution of credit to SMEs over the recent period was “demand driven” as a result of the decrease in firms’ activity and investment projects or was “supply driven” with an increase in credit “rationing” stemming from a more cautious behavior of banks. Based on a sample of around 60,000 SMEs, we come to the conclusion that, despite the stronger standards used by banks when granting credit, French SMEs do not appear to have been strongly affected by credit rationing since 2008. This result goes against the common view that SMEs suffered from a strong credit restriction during the crisis but is perfectly in line with the results of several surveys about the access to finance of SMEs recently conducted in France.